Seroepidemiology of hepatitis viruses, measles, mumps, rubella and varicella among healthcare workers and students: Should we screen before vaccination? - Aslı Karadeniz; Elçin Akduman Alaşehir (Elsevier, 2020)
Background: Health care workers (HCWs) and students are at increased risk for blood borne infections and vaccine preventable diseases (VPDs). The aim of this study was to determine the seroprevalence of antibodies against measles, rubella, mumps, varicella zoster virus (VZV), hepatitis A and B viruses among HCWs and students and to determine whether there are differences according to gender and age group. Methods: Information about characteristics of the 1053 participants, history of disease and vaccination status were collected using a structured questionnaire. Serum samples were tested for antibodies by commercial immunoenzymatic assays. Results: Seropositivity rates were 57.1% for measles, 74% for mumps, 96.3% for rubella, 93.7% for VZV, 33.9% for hepatitis A virus and 92.2% for hepatitis B virus. Susceptibility rates among participants 18-26, 27-38 and >38 years of age were statistically significant for measles (46%, 18.6% and 0%; p < 0.001) and mumps (27.1%, 12.9% and 21.4%; p < 0.05), respectively. Conclusion: Low seropositivity rates for measles, mumps and HAV are important findings. For other diseases other than VZV, it is thought that vaccination without pre-screening is more appropriate. Healthcare institutions should have policies for screening and vaccination of their staff and students. Keywords: Healthcare workers, Seroprevalence, Vaccination, Vaccine preventable diseases